Some Hydroids (Cnidaria, Hydrozoa) from the Great Australian Bight in the collection of the South Australian Museum - Watson, Jeanette E. (Zootaxa, 2018)
This report adds to knowledge of the shelf hydroid fauna of the Great Australian Bight. Hydroids were collected by the South Australian Museum and Department of Primary Industries of South Australia (PIRSA). Well known species are annotated, poorly known species are redescribed and four new species are described.